Did Ancient Egyptian Ships have Keels? The evidence of Thonis‐Heracleion Ship 17. (6th November 2014) - Belov, Alexander
<x xml:space="preserve">Abstract</x> This paper presents the debate over the presence or absence of keels in the construction of Egyptian ships of the dynastic period. It contains an analysis of ship representations and models dating to the 18th–20th dynasties of the New Kingdom (c.1539–1077 BC) that provide evidence for the introduction of keels in Egyptian shipbuilding, and new archaeological material from excavations at Thonis‐Heracleion that sheds more light on the question.